2022 44th Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2022
DOI: 10.1109/embc48229.2022.9871440
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble of Deep Learning Frameworks for Predicting Respiratory Anomalies

Abstract: This paper evaluates a range of deep learning frameworks for detecting respiratory anomalies from input audio. Audio recordings of respiratory cycles collected from patients are transformed into time-frequency spectrograms to serve as front-end two-dimensional features. Cropped spectrogram segments are then used to train a range of back-end deep learning networks to classify respiratory cycles into predefined medically-relevant categories. A set of those trained high-performance deep learning frameworks are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Pham et al [14] introduced a novel approach by merging deep learning frameworks to predict respiratory anomalies, including inception-based and transfer learning-based models. The results demonstrated that this ensemble approach outperformed existing state-of-the-art systems, promising advancements in respiratory anomaly detection.…”
Section: Related Workmentioning
confidence: 99%
“…Pham et al [14] introduced a novel approach by merging deep learning frameworks to predict respiratory anomalies, including inception-based and transfer learning-based models. The results demonstrated that this ensemble approach outperformed existing state-of-the-art systems, promising advancements in respiratory anomaly detection.…”
Section: Related Workmentioning
confidence: 99%
“…The use of machine learning has become increasingly promising for the detection and monitoring of respiratory illnesses. A recent work (Pham et al, 2022) presented an exploration of various deep-learning models for detecting respiratory anomalies from auditory recordings. Authors used the ICBHI 2017 (Rocha et al, 2019) There are also recent datasets for respiratory diseases, such as COUGHVID (Orlandic, Teijeiro, & Atienza, 2021) and Coswara (N. Sharma et al, 2020).…”
Section: Machine Learning Datasets For Respiratory Diseasesmentioning
confidence: 99%
“…In this case, typical features are matrix-like representations of the signal in a frequency-time space. Usually, FFT-based representations are extracted and used as an input for training deep learning networks, such as MLP [9], CNN [8,9,21], RNN [22], and other neural architectures [23,24]. In some works, multiple type of features are used with exceptional results [9,29].…”
Section: # Of Observationsmentioning
confidence: 99%
“…STFT+Wavelet [28] 0.78 0.20 0.49 Boosted Tree [6] 0.78 0.21 0.49 Ensemble DL [24] 0.86 0.30 0.57 Proposed Method 0.33 0.80 0.57 * 2 classes LSTM [22] 0.85 0.62 0.74 80/20 To the best of our knowledge, this is the first time that the detection of respiratory diseases is faced from an anomaly detection perspective. Interestingly, the proposed model achieved state of the art results in a patient-independent experimental protocol even though it is only weakly-supervised.…”
Section: /40 4 Classesmentioning
confidence: 99%